Improving Mathematical Skills of Mathematics Education Students Through Integrated Use of Graphing Software and Programming Techniques - Xu, Chunming (Ilmu Inovasi Nusantara, 2025)
In mathematics education, deepening the understanding of secondary school mathematics is crucial for developing prospective teachers' teaching capabilities and practical skills. While traditional teaching methods support mastering foundational concepts, future educators need varied approaches to present these concepts in real-world classrooms effectively. This study explores the effectiveness of integrating graphing software, such as Geometer's Sketchpad, alongside programming techniques in revisiting core topics within plane analytic geometry, using specific high school mathematics problems as examples. To achieve this, we employed a mixed-methods approach, combining qualitative assessments of students' conceptual understanding with quantitative evaluations of their operational skills and engagement. Students were tasked with problem-solving exercises that leveraged graphing and programming tools, promoting a more profound, intuitive grasp of geometric properties and improving their ability to simplify complex calculations. Graphing software allowed for dynamic demonstrations, enhancing comprehension of geometric relationships, while programming techniques streamlined calculations, fostering clarity and efficiency in mathematical problem-solving. The results reveal that integrating graphing software and programming approaches strengthens students' practical skills and fosters a more interactive and effective teaching style. The study recommends adopting these technologies in mathematics teacher education programs to enrich students' comprehension of mathematical concepts and boost their teaching confidence. These findings suggest that a combined approach using modern technology equips future teachers with valuable tools, enhancing their mathematical proficiency and capability to deliver impactful education.